2017
DOI: 10.1155/2017/8476258
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Tensile and Compressive Mechanical Behaviors of C-S-H Structure via Atomic Simulation

Abstract: An atomic scale model of amorphous calcium silicate hydrate (C-S-H) with Ca/Si ratio of 1.67 is constructed. Effects of temperature on mechanical properties of C-S-H structure under tensile and compressive loading in the layered direction are investigated via molecular dynamics simulations. Results from present simulations show that (1) the tensile strength and Young's modulus of C-S-H structure significantly decrease with the increase of the temperature; (2) the water layer plays an important role in the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In peculiar, the C-S-H gel showed heavy bi-modulus behavior [ 67 ]. The differences among the moduli in different directions were well aligned with the previous uniaxial MD simulation results [ 32 , 39 , 68 ]. The bi-modulus behavior when tested in the z-direction was mainly caused by the layout of the C-S-H layers.…”
Section: Resultssupporting
confidence: 89%
“…In peculiar, the C-S-H gel showed heavy bi-modulus behavior [ 67 ]. The differences among the moduli in different directions were well aligned with the previous uniaxial MD simulation results [ 32 , 39 , 68 ]. The bi-modulus behavior when tested in the z-direction was mainly caused by the layout of the C-S-H layers.…”
Section: Resultssupporting
confidence: 89%
“…The RDF of an amorphous system has a wave peak only in the proximity, and tends toward 1 as the radius increases [30]. Given that the ClayFF force field employed different potential energy parameters for the interlayer calcium (Ca h ) and intralayer calcium (Ca o ) in the C-S-H [31], the Ca h dominated the motion of Ca 2+ ions within the model. Therefore, the RDF was analyzed in this paper by counting the Ca h .…”
Section: Analysis Of Interaction Mechanismsmentioning
confidence: 99%
“…Sci. 2023, 13, x FOR PEER REVIEW 7 of 12 energy parameters for the interlayer calcium (Cah) and intralayer calcium (Cao) in the C-S-H [31], the Cah dominated the motion of Ca 2+ ions within the model. Therefore, the RDF was analyzed in this paper by the Cah.…”
Section: Analysis Of Interaction Mechanismsmentioning
confidence: 99%
“…Hou et al (2014a) investigated the mechanical and structural character of C-S-H with different interlayer water content, and they found that lower water content can result in a higher strength and modulus. In addition, the decomposition of the hydroxyl group and water evaporation induced by high temperature can considerably influence the mechanical property of the C-S-H grain (Zhang et al, 2020a(Zhang et al, , 2021a(Zhang et al, , 2021b, and the interlayer water has a primary effect on the cohesive force between solid C-S-H grains and the mechanical property of the C-S-H grain-both at ambient (Hou et al, 2014a(Hou et al, , 2014bManzano et al, 2009;Rivas Murillo et al, 2017;Xin et al, 2017;Zhou and Liang, 2019) and high temperature levels (Bonnaud et al, 2013;DeJong and Ulm, 2007;Li et al, 2017). Furthermore, Yang et al (2021) investigated the effect of the dehydration and dihydroxylation on the evolution of mechanical properties of C-S-H.…”
Section: Introductionmentioning
confidence: 99%